Modelagem do impacto do uso e manejo do solo nos processos hidrológicos e erosivos em pequenas bacias hidrográficas - Silva, Thais Palumbo (2022)
Hydrological and soil erosion processes are affected by numerous factors such as land use and soil management. Understanding the impact of land use and management on hydrological and soil erosion processes at the watershed scale depends on several environmental interactions. Hydrological models are tools to represent these interactions in space and time by detecting the main processes in different time scales and by simulating scenarios with different conditions. Therefore, the objective of this study was to understand the impact of land use and soil management on hydrological and soil erosion processes in small watersheds through monitoring techniques and hydrological modeling. Two studies were carried out in four small watersheds (~1 km2), located in the plateau and “Campanha” regions of Rio Grande do Sul state, Brazil. The first study (paper 1) quantified the impact of land use in four small watersheds under the three main economic uses (agriculture, pasture, and planted forest) in three-time steps (monthly, daily, and hourly) using the SWAT model. The SWAT model performed well in all watersheds and time steps. The agricultural watersheds showed the highest sediment and water yield values compared to Grassland and Planted Forest watersheds. The main detected hydrological processes varied in the different time steps and watersheds. Hourly dominant processes were linked to soil properties, and monthly and daily dominant processes were associated with subsurface water flow. The second study (paper 2) evaluated the effects of different conservation measures (soil management, vegetative practices and mechanical methods) in two paired agricultural watersheds: nine scenarios with individual conservation measures and four with association of the different conservation measures approaches. The crop rotation and cover crops were the best individual measures to reduce soil erosion in both watersheds. However, the association of conservation measures showed increased effectiveness to reduce sediment yield, especially the association of the three conservation approaches. The association of the three approaches reduced soil erosion by up to 60% in sub-watersheds and optimize water balance components. The outcomes of these studies indicate that land use and soil management are factors that directly affect hydrological and soil erosion processes in different time and space scales. Furthermore, modeling at the watershed scale is a viable tool to disseminate adequate land use and soil management, and to decrease impacts on soil and water degradation.